The Contribution of Fatigue to the Physical and Technical Improvement of Potential Young Athletes (Slompn) Training Center of Semarang State University - Rahayu, Tandiyo; Aji Putra, Ranu Baskora; Hadi, Hadi; Sobihin, Sobihin; Rahardian, Bayu; Guniandi, Beben; Giang, Nguyen Tra (Department of Physical Education, Sport, Health and Recreation, 2023)
The purpose of this study was to analyze the contribution of athlete fatigue levels to the physical and technical improvement of UNNES Center student athletes. This research design is ex post facto with research subjects as many as 19 young athletes aged 13-15 years at the UNNES training center within a period of 7 months. The results showed that there was a variable influence of fatigue level on physical improvement by 72% and the lack of influence of fatigue level on sports technique showed an r value of 0.287. Conclusion Long-term training centers can improve physical quality and technique by being programmed to regulate fatigue levels as a result of exercise.